Understanding students' motivations for participating in a mindfulness course: a qualitative analysis of medical students' views - Cloé Brami; Serge Sultan; Léonore Robieux; Marie-Aude Piot; Honorine Gartili; Franck Zenasni (BMC, 2023)
Abstract Objectives Improving medical students' wellbeing and empowerment through curricular activities is a topic of interest worldwide. Mindfulness-based interventions (MBIs) are increasingly implemented in medical education often as part of elective courses. To better understand training outcomes and adjust curriculum to students' needs, we will explore why will medical students participate in meditation-based education? Methods We analyzed 29 transcripts from the first session of an 8-week MBSR program offered to medical students in French. Transcripts were coded and analyzed using a qualitative content thematic analysis and the constant comparison method. Results Analyses resulted in three themes describing students' motivation: (1) Medical education and the physician's role, i.e. improving interpersonal skills, acquiring skills oriented toward a more integrative medicine, being more productive in a highly competitive context. (2) Caring for my health i.e. aiming at stress reduction, emotion regulation, and improving self-compassion. (3) A quest for meaning, i.e. optimizing meaning of care, and meaning of life. Conclusion The results highlight the congruence between the perceived motivations and the evidence on the effect of mindfulness on self-care, the development of humanistic medical skills, and the meaning of care. Some findings raise the issue of the limits of using mindfulness to enhance one's productivity. Notably, participants articulated the need for self-care as in mindfulness training, with the ability to care for others.